1986
DOI: 10.1007/bf02673791
|View full text |Cite
|
Sign up to set email alerts
|

Effects of varied substrates on aflatoxin production byA. parasiticus

Abstract: Sterilized and nonsterilized wheat kernels, soybean seeds, sesame seeds, peanut and faba bean were infected byA. parasiticus. The chemical composition, aflatoxin content and fatty acid patterns of the seeds were determined. The aflatoxins B1, B2, G1 and G2 were detected, and the amounts of the unsaturated toxins (B1 and G1) were greater than the respective dihydro derivatives (B2 and G2). Sterilized seeds infected by the fungus contained greater amounts of aflatoxins than those infected without previous steril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Tahini (sesame butter) produced by milling of dehulled and roasted sesame seeds is widely consumed as a mixture with sweet foods such as honey and grape molasses and also is an important ingredient of halva, which is a popular sweet food in Turkey and in some Middle East countries ( , ). A. flavus and A. parasiticus have been reported to grow on sesame seed and produce aflatoxins ( ). Several survey studies on sesame seeds ( ) and tahini () have shown the extent of aflatoxin contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Tahini (sesame butter) produced by milling of dehulled and roasted sesame seeds is widely consumed as a mixture with sweet foods such as honey and grape molasses and also is an important ingredient of halva, which is a popular sweet food in Turkey and in some Middle East countries ( , ). A. flavus and A. parasiticus have been reported to grow on sesame seed and produce aflatoxins ( ). Several survey studies on sesame seeds ( ) and tahini () have shown the extent of aflatoxin contamination.…”
Section: Introductionmentioning
confidence: 99%
“…The amounts of aflatoxins produced are highly dependent upon the chemical composition of the substrate (Farag et al 1986a). Aflatoxins are hepatocarcinogens, mutagens, tetratogens, and toxins.…”
Section: Introductionmentioning
confidence: 99%
“…AFLATOXINS are metabolites of the molds Aspergiflusj7avus and A.parasiticus which can grow on a wide variety of agricultural commodities and induce undesirable effects (Farag et al, 1981a(Farag et al, , b, 1985aSanchis et al 1986). The amounts of aflatoxins produced are highly dependent upon the chemical composition of the substrate (Farag et al 1986a). Aflatoxins are hepatocarcinogens, mutagens, tetratogens, and toxins.…”
Section: Introductionmentioning
confidence: 99%